Prolonged treatment of pulmonary sarcoidosis with corticosteroids - Hoyle, Clifford (1967)
The results are described of prolonged corticosteroid treatment in 52 patients with pulmonary sarcoidosis observed for a mean duration of 10·5 years from diagnosis. Twenty of the patients were treated for less than one year, the remainder for a mean of five years. The mean length of observation after discontinuing treatment was 5·5 years. Selection of patients for treatment was based on (1) evidence from radiographic observation, even for two years or more, that the disease was progressive so that spontaneous remission was improbable; and (2) evidence of disturbed lung function, especially the onset of dyspnoea or an impaired diffusing capacity. Treatment, conveniently with prednisone at a maintenance dose of about 15 mg. daily, should be continued for at least a year and often for much longer until withdrawal is not followed by radiographic relapse. Such treatment does not increase the chance of a complete remission even when given at an early stage of the disease; and relief of dyspnoea is unpredictable and seldom considerable. But prolonged treatment will halt progressive lung destruction and appears to curb the eventual mortality.